1998
DOI: 10.1255/ejms.272
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative mass spectrometry of technical polymers: a comparison of several ionization methods

Abstract: The development of soft ionization methods such as matrix-assisted laser desorption/ionization (MALDI), electrospray ionization (ESI) and secondary ion mass spectrometry (SIMS) has led to an increased use of mass spectrometry in characterizing technical (synthetic) polymers. In this paper, we compare the relative performance of these three ionization methods for characterizing the molecular weights, polydispersities and quantification of relative amounts of polymer components in mixtures. Two polymers used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 19 publications
2
24
0
1
Order By: Relevance
“…The resulting mass spectra showed a repeating pattern every three repeat units (74 m/z) that correlated to the relative population of initiator species. Similar repeat patterns were observed by Yan et al while analyzing a series of commercially obtained PDMS samples by TOF-SIMS, matrix assisted laser desorption ionization mass spectrometry (MALDI), and electrospray ionization mass spectrometry (ESI-MS) [15]. The mass spectral results for different molecular weight PDMS samples suggested that sec-butyllithium formed different amounts of siloxanolate initiator compared with the earlier findings on n-butyllithium initiated systems.…”
Section: Inear Polydimethylsiloxane (Pdms) Is Primarilysupporting
confidence: 81%
See 1 more Smart Citation
“…The resulting mass spectra showed a repeating pattern every three repeat units (74 m/z) that correlated to the relative population of initiator species. Similar repeat patterns were observed by Yan et al while analyzing a series of commercially obtained PDMS samples by TOF-SIMS, matrix assisted laser desorption ionization mass spectrometry (MALDI), and electrospray ionization mass spectrometry (ESI-MS) [15]. The mass spectral results for different molecular weight PDMS samples suggested that sec-butyllithium formed different amounts of siloxanolate initiator compared with the earlier findings on n-butyllithium initiated systems.…”
Section: Inear Polydimethylsiloxane (Pdms) Is Primarilysupporting
confidence: 81%
“…Secondly, we wanted to determine whether the relative peak intensities at each degree of polymerization in the mass spectra were true representations of the siloxanolate initiator populations. The earlier mass spectral studies did not establish this [13][14][15]. The third issue addressed in this study was to evaluate the changes in peak intensities as a function of reaction conditions such as the polymerization time, initiator concentration, and the reaction temperature.…”
Section: Inear Polydimethylsiloxane (Pdms) Is Primarilymentioning
confidence: 99%
“…This indicates that GPC-MALDI-TOF MS effectively reports the high-mass polymers within the MWD, however the low-mass polymers are under-reported and it is proposed to be mainly due to the mass cutoff at 550 Da for the elimination of matrix interferences. Another possibility for this mass bias is that the low mass PDMS polymers have higher volatility than that of high mass PDMS polymers as suggested in a study by Yan et al [9]. Under vacuum conditions in MALDI-TOF MS experiments, some of the low mass oligomers go into the gas phase as a result of evaporation without getting ionized through the normal MALDI process.…”
Section: Comparison Of Average Mass Values By On-line Gpc-esi and Autmentioning
confidence: 99%
“…he advent of soft ionization techniques such as matrix-assisted laser desorption ionization (MALDI) and electrospray ionization (ESI) have provided chemists the ability to evaluate polymer samples with several different mass analyzers. Specifically for polysiloxane materials the information rich data obtained from such analysis has been used qualitatively for repeat unit and end group determination [1][2][3][4][5][6][7] and quantitatively for relative concentration [8,9] and average mass determination [10,11]. Several reviews appear in the literature that highlight many of the applications of polymer mass spectrometry analysis [12][13][14][15].…”
mentioning
confidence: 99%
“…Desorption of intact oligomers provides a direct measure of molecular weight distribution (MWD) from which a molecular weight average can be evaluated. According to the recent reports [21,22] on the comparison of mass spectrometric techniques, TOF-SIMS produced a result similar to electrospray ionization (ESI) and fast atom bombardment (FAB). They consistently showed lower MW averages compared with gel permeation chromatography (GPC)-deduced results, whereas matrix-assisted laser desorption/ionization (MALDI) and field desorption (FD) results are higher.…”
mentioning
confidence: 99%